Tina : the dog who changed the world - Harbison, Niall (HarperElement, an imprint of HarperCollinsPublishers, 2025)
"Hope taught me the meaning of life, Tina taught me the meaning of love. It's not everyday you meet a golden retriever in Thailand. When Niall came across a dog shackled to a short chain and in a poor state of health something reminded him of his personal battle with addiction. He knew he had to rescue her immediately--golden retrievers are rare in Thailand--but there was just something about this dog in particular that told him she was destined for more. He named her Tina, and what she did next is an incredible tale of survival, hope and love. Despite her terrible treatment at the hands of humans, she refused to distrust them or feel sorry for herself, and only opened her heart wider--always with a grin (yes dogs can smile) and a reassuring wag of her shaggy yellow tail. From the minute Tina was free of her chains, she got on with what needed to be done, inspiring a dog hospital to be built and named after her and helping dogs from all over the world--whether they're street dogs from Thailand or rescue pups in Montana. The movement behind Tina has not stopped. This is her story."--Publisher.